Peranan Institusi Penghulu Mukim Bagi Mencetus Permuafakatan Dalam Masyarakat - Syed Chear, Syed Lamsah; Mohd Yusof, Norhamidah; Nordin, Norazly (Selangor Humaniora Review, 2023)
The government spends hundreds of millions of ringgits to build public facilities such as community halls, recreational parks, walkways, road signs and so on. Yet current studies show some are poorly maintained and require an urgent overhaul. The local community is known to be able to contribute positively to the local council administration. Thus, the penghulu who is often referred to as the community leader is required to play a role in uniting both parties. The objective of this study is to find out the background of the penghulu mukim as well as to assess their skill level to initiate an engagement initiative between the community and public agencies to manage public facilities. The study is based on a spectrum model of five levels of public participation (IAP2). Analysis of data from the questionnaires showed that the penghulu has a high ability to devise an engagement strategy. On a scale of 1-7, the scores are initiating initiatives (6.36), negotiating (5.93), engaging participation (5.94), collaborating (6.39) and empowering (5.56). This study provides an opportunity for the state government to assess the need to improve the quality of services of the Penghulu institution including revision of service schemes.